2004
DOI: 10.1063/1.1802377
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture cross sections of InAs∕GaAs quantum dots

Abstract: By measuring the thermal emission rates of electrons from InAs∕GaAs quantum dots, capture cross sections in the extremely high region of 10−11–10−10cm2 have been found. These data have been confirmed by using an additional method based on a static measurement at thermal equilibrium, where the Fermi level is positioned at the free energy level of the quantum dot s shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Therefore, by careful adjustment of the filling/reverse biases, electrons from the two intrinsic s states have been resolved successfully by this technique. [19][20][21] More importantly, the DLTS technique allows reliable determination of both the spatial and energy positions of nonradiative deep levels. Walther et al 22 observed energy states approximately 400 meV below the GaAs conduction band edge in or near the quantum dots, and Wang et al 6 and Krispin et al 23 reported a series of defect states in their InAs/ GaAs structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, by careful adjustment of the filling/reverse biases, electrons from the two intrinsic s states have been resolved successfully by this technique. [19][20][21] More importantly, the DLTS technique allows reliable determination of both the spatial and energy positions of nonradiative deep levels. Walther et al 22 observed energy states approximately 400 meV below the GaAs conduction band edge in or near the quantum dots, and Wang et al 6 and Krispin et al 23 reported a series of defect states in their InAs/ GaAs structures.…”
mentioning
confidence: 99%
“…The electrical space-charge technique, deep level transient spectroscopy ͑DLTS͒, 14 has recently been used to characterize QD structures, but most efforts have been focused on the intrinsic QD states. [15][16][17][18][19][20][21] The electrons can be thermally emitted out from the dots and then be detected by DLTS only when their electronic states are lifted above the bulk Fermi level. Therefore, by careful adjustment of the filling/reverse biases, electrons from the two intrinsic s states have been resolved successfully by this technique.…”
mentioning
confidence: 99%
“…However, these optical experiments could not provide direct confirmation and information, such as the energy levels and concentrations, of possible deep levels due to their generally nonradiative nature. The electrical space-charge technique, deep-level transient spectroscopy (DLTS), has recently been used to reliably determine both the spatial and energy positions of intrinsic QD states as well as the nonradiative deep levels [7][8][9]. By carefully choosing the filling/reverse biases, electrons at the Fermi Level can charge/discharge different electronic states selectively by this technique.…”
mentioning
confidence: 99%
“…Authors of main part of papers present experimental results of the investigation of the C-V dependences for structures with QDs layers and determination such parameters of QDs, as concentration, energetic position and capture cross-section. They discussed considerably widespread peculiarities of C-V dependences of the Schottky structures with well-known shelf in such dependences connected with charge accumulation in QDs states [3][4][5][6] . A number of authors proposed some methods for the detail calculation of the capacitance and compared experimental and theoretical results [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the new abilities to accumulate the carriers of a charge in the QDs which could built into various semiconductor heterojunctions such structures are capable to show the certain physical phenomenon connected with charge of QDs and reveal some specific features in capacitance-voltage (C-V) dependences [1][2][3][4][5][6] . Authors of main part of papers present experimental results of the investigation of the C-V dependences for structures with QDs layers and determination such parameters of QDs, as concentration, energetic position and capture cross-section.…”
Section: Introductionmentioning
confidence: 99%